Success outcome of reduction in anterior shoulder dislocation by FARES method - Vasudevan, Thirunarayanan; Ramlal, Ramprasath Dhurvas; Samraj, Arularasan (International Journal of Research in Medical Sciences, 2017)
Background: Acute anterior shoulder dislocation is the commonest major joint dislocation. Various reduction techniques are available and the individual preferences vary. The aim of our study was to assess the success rate and safety of FARES (Fast, Reliable and Safe) method in reduction of acute anterior shoulder dislocation. The duration of reduction, the intensity of pain experienced by patients during reduction and the factors affecting both were also assessed. Methods: A total of 161patients with acute anterior shoulder dislocation from June 2013 to May 2015 were studied. All patients underwent reduction of their dislocation by FARES method, without anaesthesia. A visual analogue scale was used to determine the intensity of pain felt during reduction. Results: 149 cases were successfully reduced by FARES method. In the remaining 12 cases closed reduction was achieved under anaesthesia. The success rate of reduction that can be achieved by FARES method was 92.54%.The mean duration of reduction manoeuvre was 1.42 mins±31 seconds and among the studied factors, age had a statistically significant influence on duration of reduction (beta 0.370; p<0.05) .The mean visual analogue pain score was 1.78 ± 0.97and among the studied factors, age had a statistically significant influence on pain perception (beta 0.013; p<0.05).No complications were encountered in any patients. Conclusion: Reduction of acute anterior shoulder dislocation by FARES method yields higher success rate in a quick time with less discomfort to the patients and without any complications.